Solid dispersions with hydrogenated castor oil increase solubility, dissolution rate and intestinal absorption of praziquantel - Chaud, Marco Vinicius; Tamascia, Pollyanna; de Lima, Andrea Cristina [UNESP]; Paganelli, Maria Ondina; Gremião, Maria Palmira Daflon [UNESP]; de Freitas, Osvaldo (Universidade de São Paulo (USP), Conjunto Quimicas, 2010)
The solubility behavior of drugs remains one of the most challenging aspects in formulation development. Solid Dispersion (SD) has tremendous potential for improving drug solubility. Although praziquantel (PZQ) is the first drug of choice in the treatment of schistosomiasis, its poor solubility has restricted its delivery oral route. In spite of its poor solubility, PZQ is well absorbed in the gastrointestinal tract, but large doses are required to achieve adequate concentration at the target sites. The aim of this study was to improve the solubility and dissolution rate of PZQ and to evaluate its intestinal absorption. SDs were formulated with PEG-60 castor oil hydrogenated (CR-60) using a fusion and evaporation method. Pure PZQ and physical mixtures (PM) and PZQ-CR-60 (2:1; 1:1; 1:2 ratios) were compared as regards their solubility, dissolution and intestinal absorption. The experimental results demonstrated the improvement in the solubility, dissolution rate and intestinal absorption. In addition, the solubility behavior showed pH dependency and that the solubility of PZQ was slower in acidic medium than in neutral and basic mediums. The increase in PZQ solubility of the SD with the CR-60 could be attributed to several factors such as improved wettability, local solubilization, drug particle size reduction and crystalline or, interstitial solid solution reduction.

A solubilidade de fármacos ainda é um dos principais desafios no desenvolvimento de formulações farmacêuticas. As dispersões sólidas (DS) apresentam grande potencial para melhorar a solubilidade de fármacos. O praziquantel é o fármaco de primeira escolha no tratamento da esquistossomose, contudo a baixa solubilidade em água restringe seu uso à administração pela via oral. Apesar da baixa solubilidade, o PZQ é bem absorvido através do trato gastrintestinal, mas doses orais elevadas são requeridas para garantir concentrações suficientes de fármaco para o tecido alvo. O objetivo deste estudo foi melhorar a solubilidade, a dissolução e avaliar a absorção do PZQ. As DS foram formuladas com óleo de castor hidrogenado - PEG 60 (CR-60), pelo uso dos métodos de fusão e evaporação do solvente. PZQ puro, mistura física (MF) e DS de CR-60-PZQ (1:2; 1:1; 2:1) foram comparados quanto à solubilidade, dissolução e absorção intestinal. Os resultados experimentais mostraram aumento na solubilidade, na taxa de dissolução e na absorção intestinal do PZQ nas DS. A solubilidade do PZQ foi maior em meio ácido, mostrando uma dependência do pH. O aumento na solubilidade do PZQ nas DS com CR-60 foi atribuída a fatores como aumento da molhabilidade, solubilização local, redução granulométrica e redução da cristalinidade ou, ainda, a ocorrência de uma solução sólida intersticial.
Keywords: Solid dispersion; Praziquantel/dissolution rates; Praziquantel/solubility; Praziquantel/intestinal absorption